RETHINKING HARDOWN HILL: OUR WESTERNMOST EARLY ANGLO-SAXON CEMETERY?. (1st July 2014) - Austin, Matthew
<x content-type="archive" xml:space="preserve">Abstract</x> This paper reassesses the early Anglo-Saxon assemblage from Hardown Hill, Dorset. Wingrave excavated the objects in 1916 but apart from his 1931 report, and Evison's 1968 analysis, there has been little subsequent discussion. Despite a lack of human remains, the assemblage has been interpreted as representing an early Anglo-Saxon cemetery – our westernmost burial site by a considerable distance and one that pre-dates the historically attested seventh-century expansion of Wessex. The following typological reclassification and contextual analysis casts serious doubts on a funerary context. Instead, an alternative interpretation is presented that views the assemblage as a useful collection of metalwork, intended to be reforged and recycled, which was presumably deposited for safekeeping and never retrieved. Such a reinterpretation highlights the need for a critical reappraisal of material from older excavations. It also has implications for our understanding of post-Roman Dorset, and for the distribution of fifth- and sixth-century Anglo-Saxon material culture more broadly.